Peran Kepala Sekolah dalam Meningkatkan Kompetensi Pedagogik Guru Di Tk Tunas Bangsa1, Ungaran Barat Kabupaten Semarang - Rochmah, Siti (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The aim of this research is to describe (1) the role of the principal as an educator in improving the pedagogical competence of teachers at Tunas Bangsa 1 Kindergarten West Ungaran, Semarang Regency, (2) the role of the principal as administrator in improving the pedagogical competence of teachers at Tunas Bangsa 1 Kindergarten, West Ungaran, Semarang Regency, and (3) the role of the principal as a manager in improving the pedagogical competence of teachers at Tunas Bangsa 1 Kindergarten, West Ungaran, Semarang Regency. This research uses a qualitative approach, namely a research process that is carried out fairly and naturally in accordance with objective conditions in the field without any manipulation (Arifin, 2018: 140). Meanwhile, the type of research is a case study, namely research that aims to study intensively about certain social units, which include individuals, groups, institutions and society (Raco, 2020: 49). The subjects of this research are school principals, teachers and school committee members or students' parents. Data collection techniques are interviews, documentation and observation. The data analysis used is qualitative analysis including data collection, data reduction, data display and drawing conclusions. The results of the research show that (1) the role of the principal as an educator in improving teachers' pedagogical competence is quite good, namely: (a) providing guidance and direction in teaching and reprimanding teachers if there are problems, (b) the efforts made are by involving teachers. teachers in training activities, KKG and providing opportunities for teachers to continue their studies to a higher level, (c) guiding teachers in the learning evaluation process through learning evaluation meetings. (2) the role of the principal as an administrator in improving teachers' pedagogical competence includes: assisting teachers in planning teaching programs, coordinating the distribution of teaching tasks, helping to improve teaching skills, and helping to manage assessments. (3) the role of the school principal as a manager in improving teacher pedagogical competence, namely carrying out planning, organizing, implementing and evaluating learning.